Teaching pragmatics through translation exercises - Díaz Ferrero, Ana María; Severino, Isa Vitória; Porlán Moreno, Rafael (Diacrítica, 2022)
Knowledge of pragmalinguistic factors is essential if a thorough command of a language is sought. In this paper we present a virtual interaction project involving Portuguese students studying Spanish as a Foreign Language (SFL) from the Marketing, Management and Accounting degree at the school of Technology and Management of Guarda (Portugal), and Portuguese as a Foreign Language (PLE) students from the Translation and Interpretation degree at the University of Granada (Spain). First, we reflect on the importance of mastering pragmalinguistic factors while learning a foreign language, especially regarding the training of future translators and interpreters, as well as with regards the training of marketing professionals and business managers. Next, we define the concept of pragmatic failure. Finally, we depict the characteristics of a teaching unit, designed by us and based on a live practice of virtual interaction among all our students that aims to develop their pragmatic competence while they carry out an exercise of contrastive analysis and translation exercises.